AB0784 Adherence rate to conventional dmards in patients with rheumatoid arthritis using biologics in a real-life setting. (23rd January 2014) - Santos-Moreno, P.; Villarreal, L.; Sandoval, C.; Real, A. P.; Boon, P.; Palomino, A.
Abstract : Background: Clinical response in patients with rheumatoid arthritis (RA) using biologicals is better when they are used in combination with conventional drugs such Metothrexate, Leflunomide or others. However, observations in cohorts of patients with RA found a percentage of them who are not really adhering to conventional DMARDs, which could have implications in treatment decisions. Objectives: The aim of this study was to describe general adherence rate to conventional DMARDs in patients using biologics and risk factors associated. Methods: A descriptive cross-sectional study was performed. Patients with diagnosis of RA and using biologicals in a large real-life cohort were included. A standardized survey was applied to patients about real adherence to conventional DMARDs. Were included patients with at least 6 visits to rheumatologist. We calculated percentages and averages. Descriptive epidemiology was applied for continuous variables, using measures of central tendency and dispersion for categorical and qualitative variables by averages and percentages. By means of pearson's statistics it was analyzed bi-variated correlations. Results: 254 patients were included, 215 (84.6%) women and 39 (15.4%) men. Majority (97.6%) of patients had established long-standing disease with a mean of 19±10 years; regarding level of education illiterate were 10.2% of patients, had elementary school 54.3%, high school 20.9%, technical 4.3% and university 10.2%; 75.6% of patients were in treatment also for other diseases; of them 69% had no-autoimmune disease and 31% another autoimmune disease. Regarding type of biologic 60.6% of patients were in anti-TNFs, 24.8% in rituximab or abatacept and 14.6% in tocilizumab. Patients were using DMARDs in 94% of cases: 1 DMARD in 9.8% of cases, 2 DMARDs in 42.3% and more than 2 DMARDs 42.3%. Regarding to adherence to conventional DMARDs: 74.8% of patients reported having difficulty to remember dose and frequency, 30.7% forgetting to take medications, 21.6% fearing potential adverse events, 20.5% feeling about taking many medications. It was acknowledged that when patients feel better: stop taking medications in 21.3% of cases or decrease the dosage in 37.4% of cases. It was established a correlation between patient's level of education and having difficulty to remember dose and frequency (p < 0.035), forgetting to take medications (p < 0.008), decrease the dosage (p < 0.001). Also was established correlation between presence of comorbidities and forgetting to take medications (p < 0.002), also between use of more than 2 DMARDs and forgetting to take medications (p < 0.046). Conclusions: Study shows more than 70% of patients with RA using biologics reported having difficulty to take associated medications (DMARDs) because many causes. Level of education and presence of many comorbidities difficult use of conventional DMARDs, which implies that biological monotherapy could be very useful in these patients. Disclosure of Interest: None Declared